2001
DOI: 10.1016/s0921-5093(01)00977-7
|View full text |Cite
|
Sign up to set email alerts
|

In-situ STM studies of strain-stabilized thin-film dislocation networks under applied stress

Abstract: OSTJThe effect of uniaxial applied stress on dislocation networks present in the atomic surface layer ofAu(111 ) was studied. The measurements were made using a novel instrument combining ultrahigh vacuum scanned-probe microscopy with an in-situ stress-strain testing machine. The technique provides microscopic information, up to atomic resolution, about the large scale plasticity of surface layers under applied loads. The herringbone reconstruction of the Au{111) surface is a classic example of a strain stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 9 publications
3
22
0
Order By: Relevance
“…The herringbone reconstruction is categorically similar from surface to surface, but each surface, and indeed each region of the same surface, has its own fine structure depending on how the discommensuration lines bend and how they interconnect. The discommensuration lines have been shown to switch direction when under external forces from the STM tip [36] or mechanical stress supplied through the substrate [37]. All these are consistent with the picture that Au(1 1 1) can organise surface atoms into a particular arrangement depending on the nature of the external influence, the adsorption of C 60 .…”
supporting
confidence: 74%
“…The herringbone reconstruction is categorically similar from surface to surface, but each surface, and indeed each region of the same surface, has its own fine structure depending on how the discommensuration lines bend and how they interconnect. The discommensuration lines have been shown to switch direction when under external forces from the STM tip [36] or mechanical stress supplied through the substrate [37]. All these are consistent with the picture that Au(1 1 1) can organise surface atoms into a particular arrangement depending on the nature of the external influence, the adsorption of C 60 .…”
supporting
confidence: 74%
“…22,23 The reconstruction shows a large-scale ordered pattern that is mediated by long-range elastic lattice strain. A recent paper 24 has shown that the herringbone not only reacts to local stress variation, but is also sensitive to the overall surface stress. Already Barth et al 22 speculated that the herringbone pattern might be used as a probe to elucidate the local distortion field in the vicinity of defects on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, in the case of Au(111) film on mica substrate, the surface reconstruction exhibits clear one-dimensional features with discommensuration lines running along the direction while the bulk-like face-center-cubic (fcc) and faulted hexagonal-close-packed (hcp) domains stack alternately along the close-packed [1-10] direction ( Figure 1(b)). 38 The lack of elbows, where stress relief is expected, signifies the tensile strain in Au(111)/mica. 39 It is generally believed that either the surface-adsorbate coupling or the surface reactivity increases with the tensile strain, 40 accompanying an up-ward shift of the metal d bands (d-band model).…”
mentioning
confidence: 99%